1986
DOI: 10.3358/shokueishi.27.375
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogenicity of Diarrhetic Shellfish Toxins in Intestinal Models

Abstract: Enteropathogenicityof diarrhetic shellfish toxins (DST) was evaluated in rabbit intestinal loops, mouse intestinal loops and suckling mice, by using the methods established for the detection of bacterial enterotoxins.Crude toxin of DST (cr-DST) was prepared by acetone extraction from scallops (Patinopecten yessoensis) implicated in the poisoning outbreaks in Osaka in 1978 and 1982. Individual DSTs such as dinophysistoxin-1 and -3 (DTX-1 and DTX-3), pectenotoxin-1 (PTX-1) and okadaic acid were also tested on su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
3

Year Published

1990
1990
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 0 publications
2
17
0
3
Order By: Relevance
“…Injection of OA and other diarrhoeic shellfish toxins into mice causes vessel congestion and extravasation into the lamina propria (Hamano et al, 1986;Terao et al, 1986), and instillation of DTX1 in ligated loops of the rat intestine leads to rapid fluid accumulation (Edebo et al, 1988). In line with these observations sprinkling of rat colon with OA was found to cause mucosal oedema and submucosal fluid accumulation (Hosokawa et al, 1998).…”
Section: Mechanistic Considerationssupporting
confidence: 59%
“…Injection of OA and other diarrhoeic shellfish toxins into mice causes vessel congestion and extravasation into the lamina propria (Hamano et al, 1986;Terao et al, 1986), and instillation of DTX1 in ligated loops of the rat intestine leads to rapid fluid accumulation (Edebo et al, 1988). In line with these observations sprinkling of rat colon with OA was found to cause mucosal oedema and submucosal fluid accumulation (Hosokawa et al, 1998).…”
Section: Mechanistic Considerationssupporting
confidence: 59%
“…If intoxication level is mild, the syndrome favorably evolves toward total recovery into one to three days illness. No fatalities have been recorded (Yasumoto et al, 1978;Hamano et al, 1986;Aune et al, 1998;García et al, 2003García et al, , 2004García et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Histopathological investigations in mice injected with PTX2 revealed severe mucosal injuries and fluid accumulation in the small intestine and revealed that it is hepatotoxic and induces rapid necrosis of hepatocytes. [27] In addition, PTXs show a potent cytotoxicity [20,28,29] and probably inhibit actin polymerization.…”
Section: Diarrhetic Shellfish Poisoning (Dsp)mentioning
confidence: 99%
“…The first incidence of human shellfish-related illness identified as DSP occurred in Japan in the late 1970s, where the dinoflagellate Dinophysis fortii was identified as the causative organism, and the toxin responsible was termed dinophysistoxin 1 (DTX1). [19,20] The OA class toxins are diarrhetics [20,21] and tumor promoters. [22] The mechanism of action underlying these activities is explained mainly by their potent inhibitory action against ser/thr protein phosphatases.…”
Section: Diarrhetic Shellfish Poisoning (Dsp)mentioning
confidence: 99%